The observability and controllability metrics of power system oscillations and the applications - Zhao, Chenghan; Wang, Xitian; Liu, Ziyu; Liu, Shiyu (Frontiers in Energy Research, 2023)
Power system oscillation has caused many serious accidents in renewable energy grid connection system. The concept of observability and controllability in control theory has been widely applied to power system oscillation study. In this paper, observability metric (OM) and controllability metric (CM) are defined from the perspective of oscillation modes, acting as a novel quantification method to quantify the observability and controllability of power system with distinct or repeated eigenvalues. Furthermore, in order to compare the reflection degree and control effect of signals in different oscillation modes, the mode comprehensive observability metric (MCOM) and comprehensive controllability metric (MCCM) are proposed. The proposed method shows clearer relationship between controllability/observability and oscillation modes by combining the information of conjugate eigenvalues together. The advantages of metrics are illustrated by comparing with theoretical derivations and calculation results of three traditional methods: participation factor, residue method and geometric measures. Finally, the metrics are applied to a subsynchronous damping controller (SSDC) design for better performance in oscillation monitoring and suppression. With the small-signal model and corresponding time-domain simulation, the effectiveness of the proposed method is verified.